Effect of sodium salts of branched chain volatile fatty acids on extra cellular ammonia utilization and protein production in vitro - MISRA, A K; THAKUR, S S (The Indian Journal of Animal Sciences, 2012)
Effects of Na salts of branched chain volatile fatty acids (isobutyric, isovaleratic and 2–methyl butyric) addition (@ 0.75 and 1.50%) in the substrates containing wheat straw, green fodder and concentrate mixture (40:40:20) and varying in protein content (8, 10 and 12%) and nitrogen sources (with and without urea) on dry matter digestion, utilization of extra cellular ammonia and protein production in the in vitro medium were investigated. Inclusion of BCFA in the substrate @ 0.75 and 1.50%, increased (P<0.01) the DM digestibility, ammonia utilization and protein content compared to control (0 dose). No added advantage was observed when the dose of BCFA was increased from 0.75 to 1.50%. The BCFA addition was found to be the most effective in the substrates containing 10 and 12% protein compared to 8% protein level as the higher (P<0.01) DM digestion, ammonia utilization and protein production were observed with these protein levels. All the 3 BCFA were equally effective. Substrate combinations containing urea showed higher (P<0.01) response of BCFA in vitro digestion, ammonia utilization and protein concentration. The responses of BCFA addition on in vitro degradation were more pronounced during first 24 h of fermentation compared to the later part i.e., 48 h. It may be concluded that the inclusion of sodium salts of BCFA @ 0.75 and 1.50% of the substrate, improved the DM digestion, ammonia utilization and protein production at in vitro medium. For optimum efficacy of the BCFA, the protein content of the substrate or diet should be in the range of 10 to 12% and part (up to33%) of this can be replaced by the urea.